Analysis of Green Oxidizer Utilization in Composite Propellants and Its Implications for the Resilience of National Defense Systems - Ilmi, Nurul; Siahaan, Timbul; Putra, I Nengah; Putra, Rizky Dwiandra; Haryanto, Aris (Indonesian Journal of Advanced Research, 2025)
The development of environmentally friendly propellant technology has become a primary focus in the defense industry. Composite propellants, which have traditionally relied on Ammonium Perchlorate (AP), offer high performance but pose environmental concerns due to the emission of corrosive chlorine compounds. This study aims to evaluate the potential use of green oxidizers such as Ammonium Dinitramide (ADN), Hydrazinium Nitroformate (HNF), hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), and octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX) as alternatives to AP. A qualitative literature review method was employed, drawing from various national and international scientific sources. Findings show that ADN and HNF offer promising performance and are more eco-friendly due to no chlorine emissions. However, challenges like thermal stability, hygroscopicity, and high production costs remain. This research highlights the potential of green oxidizers to reduce pollution and enhance national defense industry sustainability.